Effectiveness of Alue vera (Aloe barbadensis Miller) extract on the growth of Porphyromonas gingivalis: Efektivitas ekstrak Aloe vera (Aloe barbadensis Miller) terhadap pertumbuhan Porphyromonas gingivalis - Anggraini, Netta; Syah, Syakira Awlia; Anggestia, Wulan (Makassar Dental Journal, 2025)
The use of antibiotics in the treatment of periodontitis often causes resistance, so alternative natural ingredients are needed. Aloe vera (Aloe barbadensis Miller) contains active compounds, which have antibacterial properties. This study tested the effec-tiveness of aloe vera extract against the growth of Porphyromonas gingivalis by measuring the inhibition zone, minimum inhibito-ry concentration (MIC), and minimum bactericidal concentration (MBC). This laboratory experimental study used the disc diffu-sion method to test the inhibition zone and the dilution method to determine the MIC and MBC with extract concentrations of 3.12%, 6.25%, 12.50%, 25%, 50%, and 100%, with metronidazole as the positive control and 96% ethanol as the negative con-trol. Aloe vera extract effectively inhibited the growth of P.gingivalis. The largest inhibition zone diameter was found at a concen-centration of 100% (27.16 mm), while the lowest concentration was 3.12% (8.8 mm). The MIC value was found at 3.12%, and the MBC value at 12.50%. The higher the concentration of aloe vera extract, the greater the inhibitory effect produced. Even at 50% and 100%, its effectiveness was higher than that of metronidazole. It is concluded that aloe vera extract has potential as a natural antibacterial agent against P.gingivalis and may be an alternative in the treatment of periodontal disease.